2010
DOI: 10.1042/cbi20090138
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ethylene and nitric oxide in cell death in mastoparan‐treated unicellular alga Chlamydomonas reinhardtii

Abstract: This work demonstrates a contribution of ethylene and NO (nitric oxide) in MP (mastoparan)-induced cell death in the green algae Chlamydomonas reinhardtii. Following MP treatment, C. reinhardtii showed massive cell death, expressing morphological features of PCD (programmed cell death). A pharmacological approach involving combined treatments with MP and ethylene- and NO-interacting compounds indicated the requirement of trace amounts of both ethylene and NO in MP-induced cell death. By employing a carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…NaR activity appears also dispensable for nitrite-dependent NO synthesis in Scenedesmus (Mallick et al, 1999) but seems required for NO evolution from nitrite by C. reinhardtii cells grown in nitrogenreplete conditions (Sakihama et al, 2002). However, NO production by NaR-defective mutants has been documented during hypoxia (Hemschemeier et al, 2013a) in mastoparan-treated cells (Yordanova et al, 2010) or in iron-limited cultures exposed to CO (Liping et al, 2013). Together, these results point to the prevalence of alternative NO-producing pathways in C. reinhardtii, probably coupled to the increased catabolism of amino acids and nucleotides undergone by nitrogen-starved cells.…”
Section: Intracellular Nitrite Is the Most Likely Source Of No Producmentioning
confidence: 99%
See 1 more Smart Citation
“…NaR activity appears also dispensable for nitrite-dependent NO synthesis in Scenedesmus (Mallick et al, 1999) but seems required for NO evolution from nitrite by C. reinhardtii cells grown in nitrogenreplete conditions (Sakihama et al, 2002). However, NO production by NaR-defective mutants has been documented during hypoxia (Hemschemeier et al, 2013a) in mastoparan-treated cells (Yordanova et al, 2010) or in iron-limited cultures exposed to CO (Liping et al, 2013). Together, these results point to the prevalence of alternative NO-producing pathways in C. reinhardtii, probably coupled to the increased catabolism of amino acids and nucleotides undergone by nitrogen-starved cells.…”
Section: Intracellular Nitrite Is the Most Likely Source Of No Producmentioning
confidence: 99%
“…At this stage, we cannot yet assess properly the respective contributions to the loss of the cytochrome b 6 f complex of (1) protein posttranslational modifications (nitrosylation) that would target them for degradation and (2) activation of a NO signal transduction pathway. NO has been involved in a number of signaling pathways in C. reinhardtii, including acclimation to anaerobiosis (Hemschemeier et al, 2013a), iron homeostasis (Liping et al, 2013), cell death (Yordanova et al, 2010), copper stress (Zhang et al, 2008), and regulation of nitrogen assimilation As indicated in the balloon, NO contributes to the loss of the cytochrome b 6 f complex by tagging cytochrome b 6 f subunits and related proteins for degradation and/or by participating in a signal transduction pathway leading to gene activation and degradation of the cytochrome b 6 f complex. Enzymes or genetic contexts that favor the accumulation of nitrite and the production of NO are shown in black, while those counteracting these processes are shown in gray.…”
Section: Intracellular Nitrite Is the Most Likely Source Of No Producmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] As mentioned earlier, since Ca 2+ is known to be involved in several stress induced phenomenons of Chlamydomonas, we set out to explore the regulation of the 2 CDPKs, CDPK1 and CDPK3, under varying stress conditions by studying their transcript profiles using RT-PCR.…”
Section: +mentioning
confidence: 99%
“…The cell viability assay was performed following a previously published protocol (Yordanova et al, 2010). In brief, a stock fluorescein diacetate (FDA) (Sigma) solution was prepared in advance by dissolving 5 mg/ml in DMSO and stored at −20°C.…”
Section: Live-cell Imagingmentioning
confidence: 99%